Pyrophosphate:fructose 6-phosphate 1-phosphotransferase operates in net gluconeogenic direction in taproots of cold and drought stressed carrot plants - Kovács, Gabriella (Acta Biologica Szegediensis, 2006)
The purpose of this work was to further investigate the regulatory interplay between pyrophosphate:fructose 6-phosphate 1-phosphotransferase (PFP) and its positive effector fuctose 2,6-bisphosphate (Fru-2,6-P2) in heterotrophic tissues. Transformation of carrot plants (Daucus carota L. cv. Nantes Duke) with mutated mammalian 6-phosphofructo-2-kinase / fructose 2,6-bisphosphatase gene (6-PF-2-K/ Fru 2,6-P2 ase) produced carrot taproots which possessed between 163% and 410% of the Fru-2,6-P2 levels observed in wild-type taproots. Besides Fru-2,6-P2, the levels of 3-phosphoglycerate (3PGA) and hexose phosphates (hexose-P) showed the most significant alterations. Transgenic taproots possessed a marked increase in PFP activity that was accompanied by high 3PGA / hexose-P ratios under normal physiological conditions. Interestingly, 3PGA / hexose-P ratios became significantly lower in taproots exposed to drough or cold without any decrease in PFP activity. We suggested that changes in 3PGA /hexose-P ratios are a direct result of stimulation of PFP activity by the elevated Fru-2,6-P2 levels. The Fru-2,6-P2 -stimulated PFP operates in the glyconeogenic direction in the taproots of stressed carrot plants, whereas the glycolytic direction dominates in the non-stressed controls. This suggests that the metabolic status determining the net activity of PFP depends on the physiological stress situations and such, PFP is an important sensor of the environmental changes. Likely that PFP is also involved in mobilisation of energy reserves upon unfavourable environmental changes by promoting the re-synthesis of transportable sucrose through gluconeogenesis from accumulated starch in taproots.